Oxidative Stress and Genomic Damage Induced In Vitro in Human Peripheral Blood by Two Preventive Treatments of Iron Deficiency Anemia - Gambaro, Rocío Celeste (2018)
Iron deficiency is the most prevalent nutritional deficiency and the main cause of anemia worldwide. Since children aged 6–24 months are among the most vulnerable groups at risk, daily supplementation with ferrous sulfate is recommended by the Argentine Society of Pediatrics as preventive treatment of anemia. However, a single weekly dose would have fewer adverse side effects and has been therefore proposed as an alternative treatment. Ferrous sulfate is known by its pro-oxidative properties, which may lead to increased oxidative stress as well as lipid, protein, and DNA damage. We analyzed the effect of daily and weekly preventive treatment of iron deficiency anemia (IDA) on cell viability, oxidative stress, chromosome, and cytomolecular damage in peripheral blood cultured in vitro. The study protocol included the following: untreated negative control; bleomycin, hydrogen peroxide, or ethanol-treated positive control; daily 0.14 mg ferrous sulfate–supplemented group; and weekly 0.55 mg ferrous sulfate–supplemented group. We assessed cell viability (methyl-thiazolyl-tetrazolium and neutral red assays), lipid peroxidation (thiobarbituric acid reactive substances assay), antioxidant response (superoxide dismutase and catalase enzyme analysis), chromosome damage (cytokinesis-blocked micronucleus cytome assay), and cytomolecular damage (comet assay). Lipid peroxidation, antioxidant response, and chromosome and cytomolecular damage decreased after weekly ferrous sulfate supplementation (p < 0.05), suggesting less oxygen free radical production and decreased oxidative stress and genomic damage. Such a decrease in oxidative stress and genomic damage in vitro positions weekly supplementation as a better alternative for IDA treatment. Further studies in vivo would be necessary to corroborate whether weekly supplementation could improve IDA preventive treatment compliance in children.